Orchid endophytes fungi and their effect on growth in vanilla planifolia andrews (2012)
Endophytes are microorganisms that grow inside plant tissues without causing symptoms of disease which roots are associated with, among others, potential benefits in the defense against pathogens and increased nutrient availability. In the present study, endophytes from roots of orchids of the genus Vanilla in wild state were isolated, in order to determine their effect on plant growth of V. planifolia when inoculated into the substrate. The results showed that variables such as biomass, root length and height of the plant are affected by the inoculation of these endophytes. The effectiveness of these fungi on the plant protection or growth stimulation contributes to the generation of tools for the use of bio-inoculants. This will reduce the use of chemical inputs and promote environmentally friendly practices in farming systems of vanilla.